REVIEW OF ECOLOGICAL STUDIES ON GASTROPODS OF FERGHANA VALLEY SPRINGS, UZBEKISTAN (Intent Research Scientific Journal, 2023)
This article presents an overview of gastropod molluscs research conducted in Central Asia, Uzbekistan, and the Fergana Valley from the 18th century to the present day. German and Russian scientists conducted research with molluscs in Central Asia. The works of many collectors served as material. But there are almost no studies on molluscs distributed in springs